KARAKTERISTIK NIRA KELAPA FERMENTASI DENGAN METODA FERMENTASI MOROMI - Ade Iskandar; Luthfiano Yossy Darusalam (Jurnal Teknologi Industri Pertanian, 2020)
Coconut sap consists of around 85 % water, 14% sugar and a small amount of protein, amino acids, organic acids, minerals, dyes, and fats. It has the potential to be a fermentation medium. Fermented coconut sap is expected to be a raw material for seasoning product similar to salty-sweet soy sauce. Soy sauce is made from fermented soybeans or a mixture of soybeans and wheat. Soybeans and wheat are allergens, so many consumers who are healthy-living oriented avoide to consume them. The fermented coconut sap is free of soybeans and wheat. It was made through a one-step of moromi fermentation. The temperature (35, 45 and 55 ° C) and sea salt concentrations (25 and 35%) were used in this study to determine its effect on microbiological, physico-chemical and organoleptic characteristics of fermented coconut sap. The results showed that the moromi fermentation took place the number of microbes (TPC) increased from 91 + 46 cfu/g until the peak of growth of (1.18+0.48) x104 cfu/g on the day 35th and decreased into (1.54 + 0.19) x103 cfu/g on the 48th day; the pH level decreased from 6.37+0.84 to 4.22+0.75, the total dissolved solids increased from 39.35+0.90 % to 48.83+1.88%; reducing sugar increased from 0.13+0.01 mg/l to 1.64+0.45mg/l; colour changes from clear-yellowish to dark-brown; and the dominant volatile compounds were 2-pentanone, and 4-hydroxy-4-methyl. The treatment of differences in salt content did not affect the nature of fermented juice while temperature significantly affected the reducing sugar, colour, and TPC. Organoleptic test results showed that the fermented coconut sap at 55oC and the addition of 25% sea salt was the most preferred one. Keywords: coconut sap, fermented coconut sap, moromi, sea salt, temperature